Utility and Practicability of Nephrometry Scoring Systems in Contemporary Clinical Practice—An International Multicentre Perspective - Brendan A. Yanada; David Homewood; Brendan H. Dias; Niall M. Corcoran; Nathan Lawrentschuk; Ravindra Sabnis; Jeremy Y. C. Teoh; Dinesh Agarwal (Société Internationale d’Urologie Journal)
To conduct a multi-institutional international survey to determine the clinical utility and applicability of nephrometry scoring systems in contemporary clinical practice. Methods: A cross-sectional anonymous 15-item online survey was conducted on REDCap between January 2023 and May 2023. Survey invitations were sent via email within Australia and internationally to urologists who are either members of the Urological Society of Australia and New Zealand (USANZ) or the Urological Association of Asia (UAA) or who have direct professional relationships with their members. The survey underwent a trial run on REDCap with several urologists at our institution to test the technical functionality and comprehension prior to dissemination. Results: First, 158 responses were collected and analysed. Just over half (51%) responded that they use a nephrometry system in clinical practice, and the RENAL nephrometry scoring system is the most commonly used. Amongst respondents who use a nephrometry scoring system, 63% stated that it helps with counselling patients and 54% stated it serves as a decision-making tool on whether to perform a partial or radical nephrectomy. Furthermore, 54% use a nephrometry scoring system in surgical planning meetings, and 67% believe that it is helpful for research purposes. Common concerns included that they are too time-consuming to complete, they are unhelpful for treatment decision-making and they are only useful for research purposes. Conclusions: Nephrometry scoring systems are utilised by roughly one in two urologists in contemporary clinical practice. Further qualitative studies are required to better ascertain perspectives towards them and enhance their clinical applicability.